Predictive value of serum IgG/C3 levels for membranous nephropathy in diabetics with proteinuria and negative phospholipase A2 receptor antibody - Huan Wang; Xiao-wei Shan; De-wei Zhang (Linchuang shenzangbing zazhi)
Objective To detect the level of serum immunoglobulin （Ig）G/C3 in diabetes mellitus （DM） patients with proteinuria and negative serum T-type phospholipase A2 receptor （PLA2R） antibody and explore its non-invasive predictive value for membranous nephropathy （MN）. Methods A total of 52 DM patients with negative serum PLA2R antibody undergoing renal biopsy were retrospectively reviewed. The eligible subjects were assigned into two groups of diabetic kidney disease （DKD, n = 22） and MN with/without DKD （MN±DKD, n = 22） according to clinicopathological characteristics. Risk factors for MN were evaluated by multivariate Logistic regression analysis. The optimal predictive value for IgG/C3 was estimated by receiver operator characteristic （ROC） curve. Results Blood urea nitrogen was significantly higher in DKD group than that in MN±DKD group [（9.34±3.48） vs （6.88±2.44） mmol/L] （P＜0.05）. Blood creatinine became markedly elevated in DKD group than that in MN±DKD group [（159.68±94.08） vs （102.20±53.94） μmol/L] （P＜0.05）. As compared with MN±DKD group, IgG[（8.45±2.12） vs （5.85±2.65） g/L]（P＜0.01）, IgG/C3[（7.57±2.05） vs （4.66±1.77）]（P＜0.01）, diabetic duration [（7.11±6.02） vs （3.80±4.34） year] （P＜0.05） and proportion of DKD （72.73% vs 18.18%）（P＜0.01） were all significantly higher in DKD group than that in MN±DKD group. Multivariate Logistic regression indicated that serum IgG/C3 level （OR = 0.411, 95%CI: 0.185-0.910, P = 0.028） was an independent predictor of MN in diabetics. ROC curve indicated that the optimal cutoff value of IgG/C3 for predicting MN was 6.098 with a sensitivity of 77.3% and a specificity of 77.3%. And IgG/C3≤6.098 was an optimal predictor of MN in diabetics. Conclusion Lower IgG/C3 level is an independent indicator of MN in diabetics with isolated proteinuria and negative serum PLA2R antibody. Renal biopsy is recommended for these patients.